الرخصة الشرعية: تعريفها وأقسامها ومسائل تتعلق بها: Rukhsah: Definition, Division and Issues Related to It - Aḥmad bin Muḥammad bin ‘Abd al-Hādī (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
Allah SWT. has bestowed Muslims with many advantages and specialties that are not given to other people, among the greatest gifts that Allah 'azza wajalla has given to the Islamic law as well as differentiating it from the previous ummah, namely the existence of relief and eliminating distress according to the passages of the Qur'an and sunnah show this. This study aims to explain the nature of the Rukhshah Syar'iyyah (reliefs) and some of the problems associated with it and to explain the strongest opinion of the differences of opinion of the scholars. The method used in this research is the descriptive analysis method. The results of this study indicate that Rukhshah is a shar'i law that changes from difficult to easy due to an age that causes it to take this relief while still having the original legal cause. There are also some important issues related to the Rukhshah which have an impact on contemporary life. Amongthese are that the Rukhshah is a branch, not the original law and that an immoral person cannot choose an existing Rukhshah, as well as not looking for loopholes to always get one.